2020
DOI: 10.3390/ijerph17062121
|View full text |Cite
|
Sign up to set email alerts
|

A Chemically Safe Way to Produce Insect Biomass for Possible Application in Feed and Food Production

Abstract: Black soldier fly (Hermetia illucens, HI, Diptera, Stratiomydae) has great potential as a food and feed ingredient in the European Union (EU). The production of insects as livestock feed or as food ingredients requires strict monitoring of the content of potentially toxic elements (PTEs) in the growth substrate, to meet the security requirements. This study aims to investigate the presence of PTEs, like cadmium, lead, mercury, arsenic, and nickel, in HI prepupae and in their growth substrates based on coffee r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 63 publications
5
29
1
Order By: Relevance
“…Another contaminant of concern is the heavy metal content. Studies have shown that BSFL bioaccumulate certain heavy metals from their feed, with heavy metals such as cadmium, copper, lead and mercury being of particular concern due the severe health risks associated with their consumption [8,[16][17][18][19][20]. Mercury for example can have bioaccumulation factors ranging from 1.6 [17] to 4.5 [18] in BSFL, and cadmium, which is highly accumulative in BSFL, has bioaccumulation factors of between 2.5 to 9.5 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Another contaminant of concern is the heavy metal content. Studies have shown that BSFL bioaccumulate certain heavy metals from their feed, with heavy metals such as cadmium, copper, lead and mercury being of particular concern due the severe health risks associated with their consumption [8,[16][17][18][19][20]. Mercury for example can have bioaccumulation factors ranging from 1.6 [17] to 4.5 [18] in BSFL, and cadmium, which is highly accumulative in BSFL, has bioaccumulation factors of between 2.5 to 9.5 [18].…”
Section: Introductionmentioning
confidence: 99%
“…The general mean values of selenium in our study were comparable with the content of the latter element in the mealworm (Tenebrio molitor) larvae, which ranged from 0.057 to 0.085 mg kg −1 w.w. [17]. The values of the Se content in the snails of our study (0.04-0.08 mg kg −1 w.w.) were similar with those reported for pork (0.078 mg kg −1 w.w.) and beef (0.064 mg kg −1 w.w.) [18], as well as for the liver (0.06 mg kg −1 w.w.), kidney (0.41 µg/g w.w.), heart and lungs (0.05 mg kg −1 w.w.) of roe deer [19].…”
Section: Distribution Of Element Concentrations In Different Snail Timentioning
confidence: 58%
“…Cs obtained from a mixture of Robusta and Arabica varieties of roasting coffee (Saccaria caffè S.R.L., Marina di Montemarciano, AN, Italy) was used as a basal rearing substrate (control). The Cs was frozen at −20 °C and then ground to a 2 ± 0.4 mm particle size before the preparation of rearing substrates as detailed by Truzzi et al [ 9 , 24 ]. The experimental substrates were prepared by including increasing percentages (5%, 10%, 20%, and 25%) of freeze-dried S. limacinum (S) or I. galbana (I) microalgae in the basal Cs substrate.…”
Section: Methodsmentioning
confidence: 99%
“…No antibiotics were used for the commercial and experimental rearing of H. illucens larvae. The details of the rearing conditions are as reported by Truzzi et al [ 9 , 24 ]. At the end of the experiment, larvae, and frass from each of five replicates per substrate type were collected manually under sterile conditions, pooled together to reduce the effect of biological variation, and stored at −20 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation